2018
DOI: 10.12688/wellcomeopenres.14193.1
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of Anopheles gambiae sensu lato mosquito larvae in experimental aquatic habitats using environmental DNA (eDNA).

Abstract: Background: Growing insecticide resistance and changes in biting and resting behavior of malaria vectors threaten efficacy of insecticide treated nets and indoor residual spraying. Larval source management (LSM) is a promising approach that can target mosquitoes irrespective of their behavior as adults. However, the use of traditional monitoring methods for immature stages of Anopheles mosquitoes is a major challenge to LSM due to the variability in their breeding habitats.  We evaluate the use of an environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…funestus in water bodies where their larvae were not collected or identified. e previous detection of eDNA from artificial Anopheles larval habitats has demonstrated the ability to detect 0.002 larvae/ml, and further validation of our protocol with field samples is ongoing [50]. e SOPs provided and instructions on these methods should serve as good guidelines for future researchers.…”
Section: Discussionmentioning
confidence: 93%
“…funestus in water bodies where their larvae were not collected or identified. e previous detection of eDNA from artificial Anopheles larval habitats has demonstrated the ability to detect 0.002 larvae/ml, and further validation of our protocol with field samples is ongoing [50]. e SOPs provided and instructions on these methods should serve as good guidelines for future researchers.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, aquatic habitats are important for mosquito breeding. Larval source management (LSM) involves the management of water bodies that are potential larval habitats to prevent the development of immature mosquitoes into adults [18,19], and studies have shown that mosquito LSM has an important potential impact on mosquito-borne disease transmission both in urban and rural areas [20][21][22]. For example, in urban areas of Dar es Salaam, Tanzania, the use of larvicides reduced the risk of malaria infection in 5-year-old children [23].…”
Section: Introductionmentioning
confidence: 99%
“…Further development and validation of this assay could allow the identification of the different life stages of Ae. vigilax and potentially enable detection of this mosquito species larvae in water samples, as has been outlined by previous studies [ 68 ]. Aedes vigilax collected in Victoria were seen to have a high sequence identity to those of clade III, with no separation seen between individuals from the two capture locations in Victoria, indicating mixing between these populations.…”
Section: Discussionmentioning
confidence: 99%